Fertigation with alpha-tocopherol enhances morphological, physiological, and antioxidant responses in radish (Raphanus sativus L.) under drought stress - Muhammad Shahbaz Chishti; Muhammad Shahbaz; Muhammad Kaleem; Saba Shafi; Anam Mehmood; Zhang Qingzhu; Musarat Mansha; Nimra Shehzadi; Shamsa Rana; Hina Shahid; Abeer Hashem; Alanoud Alfagham; et al. (BMC Plant Biology)
Abstract Water scarcity is a foremost environmental concern and is expected to hasten in the forthcoming years due to severe fluctuations in weather patterns worldwide. The present work was designed to explore the potential role of alpha-tocopherol (α-Toc), a form of vitamin E, on the morphological, physio-biochemical, and cellular antioxidant responses of two radish genotypes grown under drought conditions (38 ± 3% of field capacity). The individual and combined applications of α-Toc (100 ppm) were used as T0- Control, T1- Control + TF (TF-alpha-tocopherol), T2- Drought (D), and T3- D + TF with three replications. In general, drought conditions cause a marked reduction in, growth traits such as root length (RL), shoot dry weight (SDW), and shoot fresh weight (SFW). However, the sole and combined applications of α-Toc significantly enhanced the SDW, SFW, and RL in both radish genotypes. Drought stress causes a significant upsurge in hydrogen peroxide (H2O2) and lipid peroxidation (LPX) in leaves. At the same time, exogenous fertigation of α-Toc protects the membranes by reducing the level of LPX, enhancing antioxidants such as catalase (CAT) and peroxidase (POX) to scavenge the reactive oxygen species (ROS), and enhancing the osmolyte as total soluble proteins to maintain cell internal osmotic potential. Also, the α-Toc enhanced the photosynthetic pigments and significantly increased photosynthetic activity in the Early Milo (G2) as compared to Laal Pari (G1) genotype under drought, enhancing water use efficiency by maintaining transpiration rate and stomatal conductance. The α-Toc also regulates the beneficial inorganic ions (K+, Ca2+, and PO₄³⁻) in the shoots of both genotypes. Our present findings demonstrate the potential role of α-Toc in mitigating drought stress and infer that it can enhance plant growth under drought conditions.